Science communication podcasting in Brazil: the potential and challenges depicted by two podcasts - DANTAS-QUEIROZ,MARCOS V. (2018)
ABSTRACT Podcasts - online distributed audio files - are easy access and production media, which can be used for Scientific Communication (SC) but few are presented in Portuguese. The objective of this work is to perform a case study with data from a survey for two Brazilian SC podcasts (Dragões de Garagem and Fronteiras da Ciência) to evaluate the increase of science podcast media in Brazil, the involved potential, their advantages, shortcomings, and perspectives. We noted an increase of listeners over the years, probably due to the internet popularization and the massive increase of mobile phones. Scientific content is underexplored, despite the great interest of the public. Humorous and informal podcasts are the most appealing to the public and they usually listen to them on informal educational sites. The majority of the public is from the South and Southeast regions, they are young male adults with undergraduate or graduate degrees. SC podcasts, despite their potential to communicate science, still have shortcomings to overcome. Nevertheless, independent initiatives can solve this difficulty, making possible for the media to reach a varied audience, affecting different groups that would not have interest in a specific content before, or even the access itself to the scientific knowledge.